Interaction Effect of Vitamin E-selenium Supplementation and Metabolic Energy on Reproductive Performance of Joper Breeders - Nining Haryuni; Hartutik Hartutik; Eko Widodo; Sri Wahjuningsih (Jurnal Ilmu Ternak dan Veteriner, 2021)
The side effect of fatty acid oxidation during lippoprotein synthesis is the release of oxygen in the tissue called reactive oxygen species (ROS). Metabolic stress in Joper brooders due to an imbalance between ROS and antioxidants causes a decrease in hatching egg production and quality. Therefore, research is needed to improve the reproductive performance of Joper broodstock by combining vitamin E-selenium supplementation and metabolic energy. This study used 200 hatched eggs resulting from a cross between 60 weeks old Sentul males and 35 weeks old ISA BROWN laying hens that had been treated. This study used a Factorial Completely Randomized Design (CRD) (2 x 4). The first factor is the energy level (2700 and 2800 kcal/kg) and the second factor is the dose of vitamin E-selenium supplementation (0, 25, 50, 75 and 100 ppm). Selenium dosage is 1ppm/mg vitamin E. The interaction between vitamin E-selenium supplementation and energy had a very significant effect (P<0.01) in increasing DOC weight. The single factor energy level and vitamin E-selenium supplementation significantly (p<0.05) in reducing embryo mortality and increasing hatchability, while fertility and eggshell quality were not affected by the two treatment factors. The conclusion of this study is the interaction between vitamin E-selenium supplementation and energy levels can increase the weight of Joper's DOC, while the single factor of vitamin E-selenium supplementation and energy levels can reduce embryo mortality and increase hatchability. The best interaction with 100 ppm vitamin E-selenium supplementation and energy 2800 kcal/kg.